The emergence of moral, professional, and political geographies in a clinically simulated parent-teacher interaction. (October 2017) - Cil, Osman; Dotger, Benjamin
Abstract: This study explored pre-service teachers' (PSTs') actions during and reflections on a clinically simulated parent-teacher interaction. We used Hargreaves's (2001a) Emotional Geographies of Teaching framework to ground and interpret the simulation data. Results indicate PSTs wrestled with the concept of professionalism, held reservations toward the actual and probable reactions of the standardized parents, and constrained both their language and actions. Our discussion centers on the presence of moral, professional, and political geographies within complex parent-teacher interactions. Implications suggest the necessity of engaging with the practice of parent/caregiver communications, as well as the emotional geographies that undergird such interactions. Highlights: Clinical simulation pedagogy is proposed as an innovative data gathering approach. The PSTs' concerns led them to modify their language and emotional responses. The PSTs questioned the boundaries between home and school.